Quality of Technology Services as a Mediator Between the Academic Environment and the Image of the Technology Campus on Student Satisfaction - Kurniawan, Arief Adhy; Pribadi, Prayoga; Sutarmin, Sutarmin (LP3M Universitas Putra Bangsa, 2024)
This study aims to conduct an analysis of the influence of academic servicescape on technology service quality and student satisfaction. This study also analyzes the influence of technology campus image on service quality and student satisfaction. This study also tested the influence of technology service quality on student satisfaction and tested the mediating role of technology service quality in the relationship between academic servicescape and technology campus image on student satisfaction. This research was conducted on students of the Digital Business Study Program at Amikom University, Purwokerto. There were 153 students who participated in this survey. The analytical method used is structural equation modeling (SEM) analysis with Smart PLS. The research results show that academic servicescape is proven to be a predictor of perceived technology service quality and student satisfaction. The study results also show that the image of a technology campus has a positive influence on the quality of technology services and student satisfaction. The results of this study also provide empirical findings that perceived quality of technology services drives student satisfaction. The results of this research also provide empirical findings that the quality of technology services acts as a mediating variable between the academic servicescape and the image of the technology campus on student satisfaction.